2017
DOI: 10.1038/ncomms14744
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide screen identifies YAP/WBP2 interplay conferring growth advantage on human epidermal stem cells

Abstract: Individual human epidermal cells differ in their self-renewal ability. To uncover the molecular basis for this heterogeneity, we performed genome-wide pooled RNA interference screens and identified genes conferring a clonal growth advantage on normal and neoplastic (cutaneous squamous cell carcinoma, cSCC) human epidermal cells. The Hippo effector YAP was amongst the top positive growth regulators in both screens. By integrating the Hippo network interactome with our data sets, we identify WW-binding protein 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
158
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(172 citation statements)
references
References 69 publications
8
158
0
1
Order By: Relevance
“…Transitions between stemness and differentiation states are determined by transcriptional and epigenetic changes that shape the genomic landscape of epithelial cells, affecting the differential binding of transcriptional activators and repressors to genes that participate in stem cell-renewal and the initiation of terminal differentiation [1][2][3] . YAP1 and its paralog TAZ (WWTR1) are co-transcriptional regulators downstream of the Hippo pathway 4,5 that are essential for skin homeostasis and epithelial stem cell maintenance [6][7][8][9] . YAP1 and TAZ are also implicated in skin basal (BCC) and squamous (SCC) cell carcinoma formation 7,10,11 .…”
mentioning
confidence: 99%
“…Transitions between stemness and differentiation states are determined by transcriptional and epigenetic changes that shape the genomic landscape of epithelial cells, affecting the differential binding of transcriptional activators and repressors to genes that participate in stem cell-renewal and the initiation of terminal differentiation [1][2][3] . YAP1 and its paralog TAZ (WWTR1) are co-transcriptional regulators downstream of the Hippo pathway 4,5 that are essential for skin homeostasis and epithelial stem cell maintenance [6][7][8][9] . YAP1 and TAZ are also implicated in skin basal (BCC) and squamous (SCC) cell carcinoma formation 7,10,11 .…”
mentioning
confidence: 99%
“…WBP2 is degraded by itchy E3 ubiquitin protein ligase (ITCH E3 ligase) to prevent aberrant growth but is protected from ITCH and activated by Wnt oncogenic signaling to drive TCF/␤-cateninmediated transcription to promote breast cancer (21). Recent studies identified WBP2 as a key cofactor of YAP driving the clonal expansion of normal and neoplastic human epidermal stem cells via TEA domain transcription factor (TEAD) transcription factors (24), in modulating G 1 /S cell cycle transition in estrogen receptorϩ breast cancer cells via a micro RNA-based mechanism (25) and crucial for normal glutamatergic synapses in the cochlea and hearing (26).…”
mentioning
confidence: 99%
“…Subsequent studies have elucidated its role as a transcription coactivator in estrogen receptor/progesterone receptor hormone signaling (5)(6)(7) and as a tyrosine kinase substrate in epidermal growth factor receptor signaling (8). It interacts with transcriptional coactivator with PDZ binding motif (TAZ), Yorkie (Drosophila YAP), and YAP, which are key downstream effectors of the Hippo pathway and which facilitate their oncogenic and growth-promoting properties (9)(10)(11). WBP2 partners with YAP/TEA domain transcription factor (TEAD) to promote epidermal proliferation required for development and wound healing (11).…”
mentioning
confidence: 99%